Improving outcomes for homeless people with alcohol disorders: a multi-program community-based approach. (1st November 2020) - Morse, Gary A.; York, Mary M.; Dell, Nathaniel; Blanco, Julie; Birchmier, Chelsea
Abstract: Background : Relatively few community-based programs have been found to be helpful for homeless people with alcohol disorders, even though this group represents a high-risk, vulnerable population prone to poor outcomes. Aims : This study sought to implement and evaluate intensive community-based programs for homeless people with alcohol disorders. Method : The project worked closely with a homeless outreach team for referrals, and then provided two different, intensive substance abuse treatment approaches matched to the needs of two subgroups: homeless individuals with alcohol disorders without severe mental illness received community reinforcement approach (CRA) and case management services, while those with alcohol and severe mental illness were assigned to assertive community treatment and integrated dual disorders (ACT/IDDT) services. The study enrolled 322 homeless people with alcohol disorders and outcomes were assessed at six months and program discharge. Results : Participants improved significantly over the first six months in a number of outcome areas, including substance abuse, mental health, housing, employment and health; progress generally remained stable between six months and discharge. Conclusions : Community-based programs that coordinate with mobile outreach teams and then provide CRA and ACT/IDDT appear to be promising approaches for helping individuals with alcohol disorders out of homelessness and into recovery.